The Beauty and the Book : Women and Fiction in Nineteenth-Century China - Widmer, Ellen (Book collections on Project MUSE., 2006)
"Chinese women entered the book trade in significant numbers in the late sixteenth century, when it became acceptable for women from "good families" to write poetry and seek to publish their collected poems. At about the same time, a boom in the publication of fiction began, and semiprofessional novelists emerged." "This study begins with three case studies, each of which probes one facet of the relationship between women and fiction in the early nineteenth century. It examines in turn the prefaces written by four women for a novel about women; the activities of a woman editor and writer of fiction; and writings on fiction by three leading literary women. Building on these case studies, the second half of the book focuses on the many sequels to the Dream of the Red Chamber, one of which was demonstrably written by a woman, and the significance of this novel for women. As Ellen Widmer shows, by the end of the century, women were becoming increasingly involved in the novel as critical readers, writers, and editors. And if women and their relationship to fiction changed over the nineteenth century, the novel changed as well, not the least in its growing recognition of the importance of female readers."--Jacket.